Management of a traumatic superior mesenteric artery injury using superselective angioembolization - Martha Ennis, MD; Jurgienne Umali, MD; David Pace, MD, FRCSC (Journal of Vascular Surgery Cases and Innovative Techniques)
We report the successful use of angioembolization to treat mesenteric bleeding in a patient who sustained blunt abdominal trauma. Angiography revealed extravasation from a distal branch of the right colic or ileocolic artery. Interventional radiology superselectively embolized a distal arterial branch supplying the ileum. Total hospital stay was 4 days. Laparotomy is the standard treatment for active mesenteric bleeding. This case highlights the usefulness of superselective embolization to mitigate the need for surgical intervention in a patient with active mesenteric bleeding. Treatment outcomes depend on close clinical monitoring for intestinal ischemia and patient counselling on the potential for surgical intervention.